The Influence of Zakat, Infaq and Shodaqoh, Human Development Index, and Poverty Level on Economic Growth in East Java - Debby Riam Larasati; Wahyuningsih, Diah; Nugroho, Ris Yuwono Yudo (Cita konsultindo, 2025)
The large potential of the Muslim population in East Java makes zakat infaq and shodaqoh an instrument of economic empowerment. This study will examine the role of zakat, infaq and shodaqoh, poverty level and HDI on economic growth in East Java. This type of research uses a quantitative approach. The research sample focuses on 29 regencies / cities in East Java Province. The research method is panel data regression method. The results showed that the zakat variable had no effect on economic growth. Infaq and shodaqoh variables have a negative and significant effect on economic growth. This influence is due to the lack of public awareness of paying zakat, infaq and shodaqoh, or already paying zakat, infaq and shodaqoh but not through zakat institutions so that the acquisition of zakat, infaq and shodaqoh is not recorded. In addition, there is a lack of supervision and socialization from zakat institutions. The HDI variable has a positive and significant effect on economic growth. Meanwhile, the poverty rate variable has a negative and significant effect on economic growth.